PEMAHAMAN MAHASISWA TERHADAP MBKM: PELAKSANAAN DAN PROGRAM MBKM - Yulinar Yulinar; Wening Nugraheni; Agus Taufiq; Yusi Riksa Yustina; Silvi Puspa Widya Lubis (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This study suggests students' understanding of the program from the Ministry of Education, namely Merdeka Learning Kurikulum Merdeka (MBKM). Understanding is examined about the implementation and programs that exist in MBKM. The research aimed to determine the understanding of the Physical Education Health and Recreation (Penjaskesrek) students of the Teaching and Education Faculty (FKIP) of Abulyatama University regarding the implementation and programs in the MBKM. The method used is descriptive qualitative, in which an online questionnaire is distributed to students taking lectures at the Physical Education Study Program, FKIP, Abulyatama University. The study results were that most of the respondents (50.9%) already knew about MBKM but did not fully understand the programs in MBKM, as much as 53%. Many respondents know about MBKM from friends and lecturers, as much as 49.1%. Respondent's interest in MBKM was 66%, and most chose to participate in apprenticeship/work practice programs, namely 47.2%. If they pass the selection, the percentage of respondents who also want to participate in MBKM activities is 78.8%. Respondents who had participated in MBKM activities were 17%, and the activities were teaching assistants and student exchanges. The support from the Study Program was also very good for students who passed MBKM. Respondents also admitted that the results of participating in MBKM could improve their soft skills. The research concludes that respondents already know about MBKM, but there are still some respondents who do not understand the MBKM program. Some respondents had passed MBKM. Support from Study Program for respondents who passed the MBKM program was very good.